2019
DOI: 10.1002/jcla.23071
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of LHPP‐associated microRNAs combined with protein induced by vitamin K deficiency or antagonist‐II in the diagnosis of alpha‐fetoprotein‐negative hepatocellular carcinoma

Abstract: Background Alpha‐fetoprotein (AFP) has received extensive attention in the differential diagnosis of hepatocellular carcinoma (HCC), especially for AFP‐negative HCC (AFP‐NHCC). The current study aimed to explore the value of targeted regulation of LHPP expression‐related microRNAs (miRs) and protein induced by vitamin K deficiency or antagonist‐II (PIVKA‐II) in the differential diagnosis of AFP‐NHCC. Methods A retrospective study was conducted on a testing set—including 214 AFP‐NHCC patients, 200 cirrhosis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Other combinations of two or three markers did not provide superior diagnostic ability. Intriguingly, it has been reported that the changes of PIVKA‐II in PHC are not associated with AFP . Therefore, PIVKA‐II can improve the positive rate of diagnosis for AFP‐negative patients.…”
Section: Discussionmentioning
confidence: 95%
“…Other combinations of two or three markers did not provide superior diagnostic ability. Intriguingly, it has been reported that the changes of PIVKA‐II in PHC are not associated with AFP . Therefore, PIVKA‐II can improve the positive rate of diagnosis for AFP‐negative patients.…”
Section: Discussionmentioning
confidence: 95%
“…A classifier established by the combination of miR-15b and miR-130b had an AUROC of 0.980 (96.7% sensitivity and 91.5% specificity) for detecting ANHC ( 44 ), and this miRNA classifier could identify 44 of 45 (97.8%) HCC cases with tumor-node-metastasis stages I and II, whereas serum AFP (cutoff value 20 ng/ml) could only detect 22 of 45 (48.9%) of the same cases; also, miR-15b and miR-130b were markedly reduced after surgery. Tian et al ( 45 ) combined miR-363-5p and miR-765 with PIVKA-II and established a logistic regression model for predicting ANHC and found that the model had the AUROC of 0.930, sensitivity of 79.4%, and specificity of 95.4% in the testing set, higher than any single indicator, and AUC of 0.936, sensitivity of 83.6%, and specificity of 94.7% in the validation set. The combination of four miRNAs (miR-125b, miR-223, miR-27a, and miR-26a) showed an AUROC of 0.849, sensitivity of 80.0%, and specificity of 89.4% for distinguishing HBV-related AFP-negative early-stage HCC and the non-cancer subjects ( 46 ); interestingly, the panel that combined two miRNAs (miR-125b and miR-27a) also had comparable diagnostic performance to the four-miRNA panel above, with an AUROC of 0.845, sensitivity of 80.0%, and specificity of 87.2% for differentiating HBV-related early-stage ANHC from non-cancer, indicating that selecting appropriate complementary biomarkers for combined detection can not only simplify detection methods but also reduce detection costs.…”
Section: Blood Biomarkers For Anhc Diagnosismentioning
confidence: 99%
“…11,12 Des-gamma-carboxyprothrombin (DCP) was once proposed to be a better HCC diagnostic marker, investigations have reported that the area under the receiver operating characteristic (AUC) of DCP is only 0.731 for diagnosing ANHCC. 13 Some other biomarkers including glypican-3, 14 Golgi protein-73 15 and micro-RNAs 16 are promising for ANHCC monitoring. However, the poorly understood pathogenesis of these molecules as well as their low specificity limit their applications in clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%